IDEAL MAKSIMAL DAN IDEAL PRIMA NEAR-RING - Saman Abdurrahman (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2010)
This study discusses the near-ring ideal covering the ideal near-ring ideal and ideal prime near-ring. Next, we studied the relationship between ideal near-ring ideal and ideal prime near-ring.